2021
DOI: 10.3897/zookeys.1047.61097
|View full text |Cite
|
Sign up to set email alerts
|

A species of the genus Panophrys (Anura, Megophryidae) from southeastern Guizhou Province, China

Abstract: Herein, we describe Panophrys congjiangensissp. nov. obtained from the Yueliangshan Nature Reserve, Congjiang County, Guizhou Province, China. Phylogenetic analyses based on the mitochondrial genes 16S rRNA and COI indicated that this new species represented an independent lineage, closely related to P. leishanensis. The uncorrected genetic distances between the new species and its closest congener, P. leishanensis, were 3.0% for 16S rRNA and 8.4% for COI. The new species is distinguished from its congeners by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Remarks: In the original description of this species, the number of male paratypes was mentioned as “15 males” in the designation while the total number of males in the type series (holotype and paratypes) was mentioned as “ n =15” in Table 5 ( Luo et al, 2021 ), which is inconsistent. The correct number of male paratypes should be “14 males” as only 14 specimens were listed in the designation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarks: In the original description of this species, the number of male paratypes was mentioned as “15 males” in the designation while the total number of males in the type series (holotype and paratypes) was mentioned as “ n =15” in Table 5 ( Luo et al, 2021 ), which is inconsistent. The correct number of male paratypes should be “14 males” as only 14 specimens were listed in the designation.…”
Section: Resultsmentioning
confidence: 99%
“…Remarks: The institute abbreviation of this species was provided as GNUG in the original description ( Zhang et al, 2017 ) but has been officially changed to GZNU ( Luo et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Navigating the intricate taxonomic history of Megophryinae, Boulenophrys has undergone several revisions despite being a relatively recent-established genus (Fei & Ye, 2016). It was frequently considered as a subgenus or synonymous of Megophrys, Panophrys, or Xenophrys (e.g., Chen et al, 2017;Luo et al, 2021;Lyu et al, 2021;Mahony et al, 2017) until Dubois et al (2021) recognized that the name Panophrys was preoccupied. They then reestablished Boulenophrys as the valid generic name following the International Code of Zoological Nomenclature.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a few new species have also been found in the northern temperate regions of Europe, Russia and China, as well as North America ( Liao et al 2021 ). Currently, there are more than 349 species of Impatiens in China ( Yuan et al, in press ) which are distributed mainly in the southwest and northwest mountainous regions, especially in southwest Provinces (including Guizhou, Yunnan, Sichuan) ( Chen 2001 ; Chen et al 2007 ; Cai et al 2015 ; Kuang 2015 ; Tan et al 2015 ; Ding et al 2016 , 2017 ; Xia et al 2019 ; Gu et al 2021 ; Liao et al 2021 ; Peng et al 2021b ; Song et al 2021a , b , c ) and 61 species of Impatiens have been reported in Guizhou Province ( Xiong and Yang 2009 ; Cong 2010 ; Kuang et al 2014 ; Luo and Deng 2015 ; Peng et al 2021a ; Yu et al 2021 ; Yuan et al in press ).…”
Section: Introductionmentioning
confidence: 99%